2016
DOI: 10.4238/gmr.15038806
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of a traditional Chinese herb, Shuangren-Anshen capsule, in a hemorrhage mouse model by using an orthogonal array design

Abstract: ABSTRACT. Shuangren-Anshen capsule (SAC) is a traditional Chinese herb that was improved in our laboratory. An orthogonal experiment [L 9 (3) 4 ] was used to optimize the extraction conditions. In vivo, a hemorrhage mouse model was established and the hemoglobin contents of normal control, model control, and treated mice were measured. Additionally, the sedative and hypnotic effects of SACs were assessed based on pharmacological parameters such as changes in locomotive activity, forelimb raising, sleep la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Therefore, our research team had used it to simultaneously isolate and quantify flavonoids complex from diverse extracts of TCM, such as Scleromitron diffusum (Willd.) R. J. Wang ( Chen et al, 2020 ) and Shuangren-Anshen capsule ( Liu et al, 2016 ). On the other hand, our research group found that the bio-enzymatic method harvests more flavonoids and higher hepatic-protective properties ( Li et al, 2016 ; Li C. et al, 2020 ) by thoroughly dissolving the cell walls of plants compared with other extraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our research team had used it to simultaneously isolate and quantify flavonoids complex from diverse extracts of TCM, such as Scleromitron diffusum (Willd.) R. J. Wang ( Chen et al, 2020 ) and Shuangren-Anshen capsule ( Liu et al, 2016 ). On the other hand, our research group found that the bio-enzymatic method harvests more flavonoids and higher hepatic-protective properties ( Li et al, 2016 ; Li C. et al, 2020 ) by thoroughly dissolving the cell walls of plants compared with other extraction methods.…”
Section: Introductionmentioning
confidence: 99%